Culture-independent detection of Mycobacterium tuberculosis complex DNA using targeted next generation sequencing in African buffalo (Syncerus caffer) oronasal swabs in South Africa - Mhlophe, Sinegugu Kholeka; Clarke, Charlene; Ghielmetti, Giovanni; Matthews, Megan; Kerr, Tanya Jane; Miller, Michele Ann; Goosen, Wynand Johan (Frontiers in Veterinary Science, 2025)
African buffaloes (Syncerus caffer) are wildlife maintenance hosts of Mycobacterium bovis (M. bovis), the causative agent of animal tuberculosis (aTB) in multiple ecosystems across South Africa. In addition to their role as keystone species, these animals are vital to South Africa’s economy as a highly valuable species. Controlling aTB in South Africa relies on mycobacterial culture as the gold standard for M. bovis confirmation, with the single intradermal comparative cervical test (SICCT) and Bovigam™ assays as validated cell-mediated immunological assays for detection. However, these methods are not without their shortfalls, with a suboptimal ability to discern true positive results amidst certain non-tuberculous mycobacteria (NTM) interference. This study employed a culture-independent approach using oronasal swabs collected from African buffaloes (n = 19), originating from three herds with no recorded history of M. bovis infection, to elucidate the possible cause of observed discordant immunological aTB test results. The DNA was extracted directly from the oronasal swabs, amplified using Mycobacterium genus-specific PCRs, then amplicons were pooled and sequenced using Oxford Nanopore Technologies (ONT) long-read platform. Mycobacterium tuberculosis complex DNA, along with various NTM species, were identified in 8/19 samples. The methods described support a more robust interrogation of the buffalo oronasal mycobacteriome. These findings highlight the value of accurately distinguishing between mycobacterial species in complex samples, especially in high-value animals, to facilitate accurate interpretation of immunological test results and management of aTB.